Respiratory Failure Following a Venomous Snakebite: Importance of Ambu Bag Ventilation in a Poor‐Resource Setting - Abdul Matin; Sarwar Alam Sobuj; Prity Saha; Chowdhury Adnan Sami (Clinical Case Reports)
ABSTRACT Venomous snakebites are critical medical emergency. Most fatalities resulted from respiratory failure attributable to abrupt neuromuscular paralysis. A 35‐year‐old male was treated for a snakebite on the dorsum of his right foot, which occurred seven hours prior to hospital admission during sleep. The patient exhibited symptoms of headache, myalgia, extremity weakness, and altered consciousness. No hemorrhagic or myotoxic symptoms were observed. He subsequently had respiratory failure, necessitating emergency bedside intubation with an Ambu bag, followed by treatment initiated in the district hospital and continued in the intensive care unit of a medical college hospital. Timely diagnosis, immediate transport to a medical facility, and rapid bedside intubation can save the lives of individuals experiencing respiratory failure due to venomous snake bites.